Capreolucanus yanxui Qi & Zhou, new species, the third species of the genus from Yunnan (China) based on morphological and molecular characters (Coleoptera: Lucanidae: Lucaninae) - Qi, Zhi-Hao; Zhou, Zheng; Su, Rong-Xiang; Duan, Lei; Zhang, Yi-Feng; Song, Hai-Tian (Zootaxa, 2024)
The third species of the small and rare stag beetle genus Capreolucanus Didier, 1928 was found from Yunnan Province, China: C. yanxui Qi & Zhou, new species. The complete mitogenome of the new species is assembled. Based on morphological characters and the mitochondrial marker COX1, the new species can be clearly distinguished from C. sicardi Didier, 1928, the most similar species. A key is provided to distinguish all known species of this genus and some new genetic and biological information of the genus are reported for the first time.